Polioencephalomalacia in a Dorper sheep – Case report (Research, Society and Development, 2026)
Polioencephalomalacia (PEM) is a neurological disorder that affects the gray matter of the brain in ruminants, characterized by cortical necrosis and central nervous system clinical signs, with significant sanitary and productive impact. Its etiology is multifactorial and mainly associated with thiamine deficiency, excessive sulfur intake, abrupt dietary changes, and metabolic disturbances, occurring as isolated cases or outbreaks. This study aims to report a case of polioencephalomalacia in a young Dorper sheep, with a presumptive diagnosis based on clinical signs and therapeutic response. A three-month-old male sheep was admitted presenting diarrhea, visual impairment, head pressing, head tilt, circling, ataxia, intention tremors, and anorexia. Physical and neurological examinations revealed central neurological impairment, associated with electrolyte imbalances identified by blood gas analysis. Differential diagnoses included traumatic brain injury, intoxications, and infectious diseases; however, due to the clinical suspicion of PEM, immediate treatment with high-dose thiamine, associated with dexamethasone, clinical support, and antiparasitic therapy, was instituted. The animal showed marked improvement in neurological signs within a few hours after treatment initiation, with complete recovery within 24 hours and clinical discharge after six days, without recurrence. The favorable outcome reinforces the importance of early clinical diagnosis and prompt thiamine administration as an essential therapeutic approach, as well as the relevance of appropriate nutritional management in preventing the disease in small ruminants.